2017
DOI: 10.3390/ijerph14080910
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Status of Health Service Utilization among Caregivers of Left-Behind Children in Poor Rural Areas of Hunan Province: A Baseline Survey

Abstract: Background: The caregivers of left-behind children (CLBC) in China’s poor, rural areas are mostly elderly and women. Their health status and access to health services have not been previously characterized. This study aims to explore the status of CLBC in terms of their health service utilization and to provide a scientific basis for guiding effective implementation of health policy in rural Hunan. Methods: Random cluster sampling was used to survey CLBC in two rural counties. Face-to-face interviews and quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…Even though health education is included in Chinese primary health care, the resources to receive health knowledge are limited. In our study, no doctor had received nutritional training before and less than a fifth of caregivers had participated in health education workshop organized by local health institutions [ 4 ]. Lack of transport facilities and cost of transport were the barriers for caregivers to access health services, including health education.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though health education is included in Chinese primary health care, the resources to receive health knowledge are limited. In our study, no doctor had received nutritional training before and less than a fifth of caregivers had participated in health education workshop organized by local health institutions [ 4 ]. Lack of transport facilities and cost of transport were the barriers for caregivers to access health services, including health education.…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional knowledge and food practice behaviors of caregivers of LBC (CLBC) directly affect children’s health. Our baseline data showed that about 75% of LBC are separated from both parents (with both parents having migrated) and that most of the caregivers are elderly grandparents (83%), or sometimes distant relatives or neighbors [ 4 ], who are less-educated and do not pay sufficient attention to dietary diversity, nutrition, and food sanitation. They have difficulties in providing children with a reasonable and nutritious meal supply.…”
Section: Introductionmentioning
confidence: 99%
“…“Caregivers thought the treatment in hospitals was ineffective” and “Inconvenient transportation” were the two main barriers to the health service utilization of LBC. Low-education levels may affect caregivers’ ability to cultivate children scientifically and to access child health services [14,15,16]. When seeking health care in rural areas, people have to face the challenge of accessibility and high transportation cost [17].…”
Section: Discussionmentioning
confidence: 99%
“…The left-behind phenomenon is driven in large part by China’s rapid development and urbanization, and in particular by the migration of large numbers of rural residents from their rural homes to urban areas in search of better job opportunities [ 2 ]. It is common for migrant parents to leave their children behind with a caregiver—typically the paternal grandparents—in their home communities [ 1 , 3 , 4 ]. This has created a new, large, and potentially vulnerable subpopulation of left-behind children in rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…One possible mechanism for lower health outcomes is that elderly surrogate caregivers may not be as proactive as parents in seeking health remediation for children. This may be especially true when considering health conditions that are not acute or have few obvious symptoms, but for which treatment can yield important gains in wellbeing and/or productivity [ 3 , 15 ]. For such conditions, preemption on the part of caregivers may factor highly in uptake of remediation.…”
Section: Introductionmentioning
confidence: 99%